2015
DOI: 10.5489/cuaj.3014
|View full text |Cite
|
Sign up to set email alerts
|

Novel survey disseminated through Twitter supports its utility for networking, disseminating research, advocacy, clinical practice and other professional goals

Abstract: Our results suggest that Twitter users in the urological community perceive important benefits. These benefits extend to multiple professional domains, particularly networking, disseminating information, remote conference participation, research, and advocacy. This is the first study that has been disseminated to targeted individuals from the urological community directly through tweets, providing a proof of principle for this research method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 15 publications
4
36
0
Order By: Relevance
“…[3][4][5][6][7] Within urology, SoMe is used to conduct an international e-journal club, 8 facilitate open-access discussions at conferences, 9,10 disseminate information from prominent journals and societies, 11 identify areas for improvement in educational resource distribution to patients, [12][13][14] rapidly and accurately assess robotic surgical suturing performance, 15 network professionally, 16 and improve response rates to surveys. 16 Due to the bourgeoning connection between SoMe and urology, a standardized nomenclature to discuss urologic topics online has been created. 17 Despite its strong vocal support, 18 SoMe's integration into urology has not been without its barriers.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Within urology, SoMe is used to conduct an international e-journal club, 8 facilitate open-access discussions at conferences, 9,10 disseminate information from prominent journals and societies, 11 identify areas for improvement in educational resource distribution to patients, [12][13][14] rapidly and accurately assess robotic surgical suturing performance, 15 network professionally, 16 and improve response rates to surveys. 16 Due to the bourgeoning connection between SoMe and urology, a standardized nomenclature to discuss urologic topics online has been created. 17 Despite its strong vocal support, 18 SoMe's integration into urology has not been without its barriers.…”
Section: Introductionmentioning
confidence: 99%
“…This is concerning in light of recent studies showing the unprofessional content present in publicly accessible social media pages for graduating urology residents and junior faculty [11]. Even among active urological Twitter users, only 65% were aware of professional guidelines related to social media use [12].…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, a multicenter randomized controlled trial, the Childhood Adenotonsillectomy Study, showed that sizable minority of children with obstructive sleep apnea have resolution of symptoms over time without surgery 7 . As such, the decision for surgery may be complex and multifaceted for the parent 8 , and they may seek information from external (e.g., online) sources to enhance their surgical decisions and knowledge 9 .…”
Section: Introductionmentioning
confidence: 99%